2020
DOI: 10.2478/johr-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Production of ‘Konstancin’ Rose Cuttings in the Growth Chamber Under Led Light

Abstract: The impact of light quality generated by light-emitting diodes (LEDs) on the adventitious root formation and cuttings’ quality of rose hip ‘Konstancin’ under controlled conditions in multilevel growth chamber without access to natural light and in the greenhouse was evaluated. In the growth chamber, the lighting was provided by a combination of red and blue LED arrays and white LED tubes, while in the greenhouse, red and blue LED lights were used as a supplement to natural light. The number of rooted cuttings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Matysiak [21] observed that the combination of light characteristics did not always result in optimal rooting percentage. The exposure of roses of the 'Konstancin' cultivar to dichromatic white + blue light resulted in a lower rooting percentage than the exposure to the monochromatic white light of high photosynthetic photon flux density (PPFD) 100 µmol m −2 s −1 .…”
Section: Rooted Cutting Activitymentioning
confidence: 99%
“…Matysiak [21] observed that the combination of light characteristics did not always result in optimal rooting percentage. The exposure of roses of the 'Konstancin' cultivar to dichromatic white + blue light resulted in a lower rooting percentage than the exposure to the monochromatic white light of high photosynthetic photon flux density (PPFD) 100 µmol m −2 s −1 .…”
Section: Rooted Cutting Activitymentioning
confidence: 99%